EXPLORING IRRITABLE BOWEL SYNDROME (IBS) AND INFLAMMATORY BOWEL DISEASE (IBD)CAUSES, DIAGNOSIS AND TREATMENT: SYSTEMATIC REVIEW - Abdulrahman Mohammed Alshamrani., Mohammed Faya Mohammed Asirri, Baiaan Hamad Alsaadi, Nasser Nijr Helal Alotaibi, Alhamidi Khaled Salem Al Harbi, Saleh Marzouq Alotaibi (Chelonian Research Foundation, 2023)
This systematic review gives the full picture and points out the difference between IBS and IBD discussing the epidemiology, pathophysiology, differential diagnosis, and treatment guidelines. IBS, a functional disease, which has either varying prevalence or higher prevalence invariably, in different parts of the world while on the other hand inflammatory IBD is a consistent higher prevalently, in the entire world with recent trends of the rise in the West. In terms of gender variations, age of onset, and socioeconomic consequences, all sides of this equation are considered. These characteristics are crucial for the differentiation of IBS and IBD. In contrast, IBD is production of autoimmune reaction in the back and end up with chronic inflammatory. The strategy for IBS management encompasses exercise, abdominal massage, diet alteration, and psychological techniques while in IBD, immune suppressors such as immune system suppressors, biologics or surgery could be considered.